The Modified Pyrolysis Process to Minimize the Energy Consumption by Preheating the Opaque Reactor using Solar Energy and Determination of Possibility in Case of using it in Diesel Engine (Global Journals of Research in Engineering, 2013)
Petroleum oil which is limited due to its reserve capacity is the prime source of fuel in the world as well as Bangladesh The concerning depletion rate of Petroleum oil leads to go for alternative fuels T bellirica bahera biodiesel is a sustainable alternative fuel and is eco-friendly though the extraction is costly Biomass is collected from Bangladeshi forest and oil is extracted from kernel containing of about 40 oil The oil is extracted by the solvent extraction process using soxhlet apparatus It has been found that the oil contains free fatty acid of about 0 87 which is turned into biodiesel by the transesterificationl by reacting methanol with lipid oil in the presence of base catalyst sodium hydroxide The physiochemical properties of Bahera Methyl Ester BME biodiesel are investigated with the various experimental processes The different physiochemical properties include density kinematic viscosity cetane number calorific value flash and fire point cloud point pour point acid value elemental analysis and boiling range The results show that all properties are compatible with standard values of other biodiesels The investigation of different performance parameters such as efficiency BSFC the temperature variation of the exhaust gas were observed for further competence of T bellirica biodiesel All those investigation stands T bellirica as a potential source of biodiesel
Keywords: T Bellirica; BME; biodiesel; physiochemical properties; transesterification; performance parameters